2013
DOI: 10.1088/1748-9326/8/4/044012
|View full text |Cite
|
Sign up to set email alerts
|

Downstream Yangtze River levels impacted by Three Gorges Dam

Abstract: Changes in the Yangtze River level induced by large-scale human water regulation have profound implications on the inundation dynamics of surrounding lakes/wetlands and the integrity of related ecosystems. Using in situ measurements and hydrological simulation, this study reveals an altered Yangtze level regime downstream from the Three Gorges Dam (TGD) to the Yangtze estuary in the East China Sea as a combined result of (i) TGD's flow regulation and (ii) Yangtze channel erosion due to reduced sediment load. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 32 publications
4
103
0
1
Order By: Relevance
“…See Table 1 for species codes the Dongting Lake being substantially modified by the Three Gorges Dam, larval fish abundance has greatly declined and the occurrence of larval fish is delayed in this river section . With a much longer distance from the Three Gorges Dam, the influences of the dam on the river section connecting to Poyang Lake are much weaker than Dongting Lake (Wang, et al, 2013). In this regard, the connectivity of Poyang Lake to the Yangtze River provides critical refuge for fishes adapting to the river-floodplain system.…”
Section: Discussionmentioning
confidence: 99%
“…See Table 1 for species codes the Dongting Lake being substantially modified by the Three Gorges Dam, larval fish abundance has greatly declined and the occurrence of larval fish is delayed in this river section . With a much longer distance from the Three Gorges Dam, the influences of the dam on the river section connecting to Poyang Lake are much weaker than Dongting Lake (Wang, et al, 2013). In this regard, the connectivity of Poyang Lake to the Yangtze River provides critical refuge for fishes adapting to the river-floodplain system.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [29] reported alterations in the regime of downstream Yangtze levels (Figure 3), resulting from both flow regulation and degradation of the channels due to reductions in the sediment load. Although the TGD releases clear water into the downstream section, the turbulent flows cause large amounts of suspended sediments to be moved downstream, changing the morphological evolution of the river channel.…”
Section: Hydrological Regimementioning
confidence: 99%
“…Overall, however, continued future erosion of the downstream channel may further act to counteract the benefits ecological obtained by increasing the Yangtze levels (by releasing TGD water) in the winter/fall, and thereby accelerate the decline in the inundation areas/levels of downstream lakes [29]. The shrunken and simplified geomorphology of the Yangtze River, due to the operation of the TGD, has been expected to have direct adverse effects on riparian ecology [13], producing spatially smaller, less diverse riparian ecosystems as compared to the pre-dam period.…”
Section: Ecology and Environmentmentioning
confidence: 99%
“…The Three Gorges Reservoir (TGR) on the Yangtze River is the largest river regulation and hydroelectric power station in the world [5]. It cost more than US $32 billion to construct and has an operational water level 110 m above the downstream river level.…”
Section: Negative Impacts From Reservoir Developmentmentioning
confidence: 99%